The answer is B. <span>the x-intercept represents Adam's total sales when he earned no commission
I took the test :3</span>
Answer:
![(y-6)^2=9](https://tex.z-dn.net/?f=%28y-6%29%5E2%3D9)
Step-by-step explanation:
Given
![y^2 - 12y = -27](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%3D%20-27)
Required
Get equivalent expression using completing the square
<em>Follow these steps:</em>
- <em>Take the coefficient of y; That is -12</em>
- <em>Divide it by 2; That is (-12/2)</em>
- <em>Square it: (-12/2)^2</em>
<em />
Add to both sides of the equation
![y^2 - 12y + (\frac{-12}{2})^2= -27 + (\frac{-12}{2})^2](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%20%28%5Cfrac%7B-12%7D%7B2%7D%29%5E2%3D%20-27%20%2B%20%28%5Cfrac%7B-12%7D%7B2%7D%29%5E2)
![y^2 - 12y + (-6)^2= -27 + (-6)^2](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%20%28-6%29%5E2%3D%20-27%20%2B%20%28-6%29%5E2)
![y^2 - 12y + 36= -27 + 36](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%2036%3D%20-27%20%2B%2036)
![y^2 - 12y + 36= 9](https://tex.z-dn.net/?f=y%5E2%20-%2012y%20%2B%2036%3D%209)
Expand the right-hand side
![y^2 - 6y - 6y + 36= 9](https://tex.z-dn.net/?f=y%5E2%20-%206y%20-%206y%20%2B%2036%3D%209)
Factorize:
![y(y-6)-6(y-6) =9](https://tex.z-dn.net/?f=y%28y-6%29-6%28y-6%29%20%3D9)
![(y-6)(y-6)=9](https://tex.z-dn.net/?f=%28y-6%29%28y-6%29%3D9)
![(y-6)^2=9](https://tex.z-dn.net/?f=%28y-6%29%5E2%3D9)
Answer:
a = 9.849
b = 20.25
c = 491.03
Step-by-step explanation:
By using Pythagoras theorem in the right triangle BDC,
(Hypotenuse)² = (Leg 1)² + (Leg 2)²
BC² = BD² + DC²
a² = 9² + 4²
a = ![\sqrt{(81+16)}](https://tex.z-dn.net/?f=%5Csqrt%7B%2881%2B16%29%7D)
a = ![\sqrt{97}](https://tex.z-dn.net/?f=%5Csqrt%7B97%7D)
a = 9.8489
a ≈ 9.849 units
By mean proportional theorem,
![\frac{\text{DC}}{\text{BD}}=\frac{\text{BD}}{\text{AD}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BDC%7D%7D%7B%5Ctext%7BBD%7D%7D%3D%5Cfrac%7B%5Ctext%7BBD%7D%7D%7B%5Ctext%7BAD%7D%7D)
AD × DC = BD²
b × 4 = 9²
b = ![\frac{81}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B81%7D%7B4%7D)
b = 20.25 units
BY Pythagoras theorem in ΔADB,
AB² = AD² + BD²
c² = b² + 9²
c² = (20.25)² + 9²
c² = 410.0625 + 81
c = 491.0625
c = 491. 063 units
Answer: A would be the answer!! :D
Answer:
A=30
Step-by-step explanation:
Set your equation up as following:
180=90+(x+37)+(x+67)
180=90+37+67+2x
180-90-37-67=2x
-14=2x
-14/2=x
-7=x
Angle A = x+37
A=-7+37
A=30